AMELIORASI BAHAN ORGANIK PADA MEDIA TAILING PASIR PASCATAMBANG TIMAH UNTUK PERTUMBUHAN BIBIT KARET - Ismed Inonu; Dedik Budianta; M. Umar Harun; Yakup Yakup; A. Y.A Wiralaga (Universitas Lampung, 2011)
The objective of this study was to evaluated some organic materials to improve the characteristics of post-mining tin sand tailings and its effect on the growth of rubber ttree. The experiment was conducted at PT Koba Tin nursery Central Bangka District during 5 months. The study was designed according to a factorial randomized completely design with two factors and three replications. The first factor was the type of organic matter ameliorant (chicken manure, oil palm empty fruit bunches compost, and municipal solid waste compost), and the second factor was the proportion of sand tailings, top soil and organic materials (2:1: 1 and 2:1:2, v/v). The results showed that growth of rubber seedlings in sand tailings media derived from tin-postmining which is ameliorated by top soil and organic materials is still lower than growth on unmined land media. The growth of rubber tree seedlings on media with two proportion of sand tailings, one proportion top soil and two proportion of empty fruit bunches compost ( 2:1:2, v/v) two better than other combinations. Key words: amelioration, manure, compost, rubber tree, sand tailings